The Multi Agent System for Job Recommendation. Issue 1 (April 2020) - Tentua, Meilany Nonsi; Azhari, Azhari; Musdholifah, Aina
Abstract: The number of available job portals causes abundant information. Therefore, a system of recommendations is needed by job seekers to find jobs that fit their profile. Offering job vacancies on job portals are changing every time because there are always additional job search data and job opening data. Multi-agents system is a technology that can be used to handle information changes. This article proposed a recommendation system is expected to help job seekers to get jobs in accordance with the field of science they have. The system will monitor what work is offered by online job portals. From the results of observations, the job content offered will be used as a reference so that if new content is entered, the agent will automatically provide input to the job seeker. Based on the results of the implementation of the recommendation system using a multi-agent system can provide search results that are in accordance with what is inputted by the user based on the profile they have. These search results can recommend jobs that match the job seeker profile.